MANAJEMEN PEMBELAJARAN KITAB TA’LIM MUTA’ALIM DALAM MEMBENTUK KARAKTER SISWA DI MA KETRAMPILAN AL-IRSYAD DEMAK - Amin, Moh (QUALITY, 2018)
This study aims to find out the concepts, policies, implementation and learning evaluation system of Ta'lim Muta'alim in shaping the character of students in MA Ketrampilan Al-Irsyad Gajah Demak. This research uses field research research and qualitative approach. Data that has been collected will be analyzed with qualitative descriptive approach to know kitab Ta’lim Muta’alim learning management in shaping the character of students in MA Skill Al-Irsyad Gajah Demak. The results of the study and discussion show that the concept of learning Kitab Ta'lim Muta'alim in shaping the character of students in MA Al-Irsyad Gajah Demak is a book study which contains about the ethics that must be possessed by the students. The learning policy is based on the importance of character building on students and also keeping the tradition of science in madrasah. Implementation of Kitab Ta'lim Muta'alim learning in shaping the character of students in MA Al-Irsyad Gajah Demak implemented through the stages of planning, organizing, actuating and assessment. And the evaluation system of learning Kitab Ta'lim Muta'alim in shaping the character of students in MA Al-Irsyad Gajah Demak consists of planning process, implementation and follow-up of learning evaluation result.Keywords: Learning Management, Kitab Ta’lim Muta’alim, Student Character